The motives for the mesarum edict of King Ammiṣaduqa of the old Babylonian period : ethics, ego or economics? - Gaertner, Lorraine (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Ancient Studies)--University of Stellenbosch, 2008.